Spiritual care: What do cancer patients and their family members want? A co-design project - Egan, Richard (Journal for the Study of Spirituality, 2018)
Purpose: Through active participant engagement, this project aimed to better comprehend the spiritual care needs of New Zealand cancer patients and their families and friends, and to gain further insight from others, including healthcare practitioners. Methods: A co-design process was undertaken, which involved presentations and interactive group workshops on the topic of spirituality and spiritual care. A facilitated, semi-structured discussion centred around three main topic areas: the meaning of spirituality; the documentation of spirituality in healthcare settings; current spiritual care development needs; and areas for improvement. The Framework Method was used to undertake an inductive analysis of the qualitative data in order to develop key themes according to topic area. Results: Key concepts constructed from our analysis of the three main topic areas include: Participants broadly understood spiritualty to be characterized by core values, expressions of love and kindness, and connectedness with others and/or with the environment; participants felt as if documentation of spiritual beliefs had the potential to inform others about their needs and wishes participants also recommended that opportunities be created for people to engage in conversation about spirituality, and that this should be undertaken purposefully. Importantly, responses often alluded to the great diversity of need when it comes to spiritual care. Conclusions: Integration of spiritual care into health system policies, intake and assessment processes, care plans, and training and professional development opportunities, are all required in order to reflect relevant national guidelines and strategies more effectively.